2022
DOI: 10.1155/2022/9983782
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Organic Fertilizer Adoption in Moretna Jeru District, Northern Ethiopia

Abstract: Agriculture is the backbone of Ethiopia’s economy. It is responsible for 35.45% of the country’s total domestic output. This means that the sector is critical for enhancing the lives of the wider population. Despite its importance, Ethiopia’s agricultural sector produces little. The Ethiopian government has focused on increasing the usage of organic fertilizers to improve this and overall economic growth. Organic fertilizer use is still inadequate in most parts of Ethiopia, including Moretna Jeru District in N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Contrary to the perceived increase in the cost of production associated with organic fertilizer adoption, as supported by the works of [36,37], the study establishes a decrease in the cost of production by adopters and also increase yield of adopters resulting in increase in proft. Te impact of organic fertilizer adoption on proft is higher than its impact on yield and income.…”
Section: Te Impact Of the Organic Fertilizer On Maize Farmmentioning
confidence: 56%
See 2 more Smart Citations
“…Contrary to the perceived increase in the cost of production associated with organic fertilizer adoption, as supported by the works of [36,37], the study establishes a decrease in the cost of production by adopters and also increase yield of adopters resulting in increase in proft. Te impact of organic fertilizer adoption on proft is higher than its impact on yield and income.…”
Section: Te Impact Of the Organic Fertilizer On Maize Farmmentioning
confidence: 56%
“…Organic fertilizer did not only increase yields but also increased farm income up to about 53% when used. Te adoption of organic fertilizer is perceived to result in increase in cost of production due to extra labour requirement and transport cost associated with the technology, as supported by the works of [36,37]. However, the fndings of [81] establish a negative relationship with the cost of production.…”
Section: Te Impact Of Organic Fertilizer On Maize Farmmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, the intensity of use of fertilizers was influenced by the status of education of the household head, family size, access to credit, membership to cooperatives, the use of crop rotation, annual income, number of farm plots owned, the use of soil and water conservation, and agroecology. Belete (2022) analyzed the factors that determine the Organic fertilizer adoption in Moretna Jeru District, Northern Ethiopia and they found that, farmers' characteristics such as extension contact, amounts of livestock, landownership via title deed, and household size have a favorable and they significantly impact on organic fertilizer usage.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The agricultural sector in Indonesia plays a crucial role in the overall economic development of the country (Belete, 2022;Bromley, 2009;Hayden et al, 2022;Saygılı & Çakmak, 2022;Tripoli & Schmidhuber, 2018). It serves as a significant source of employment, particularly in rural areas, and contributes to the livelihoods of millions of people (Armoogum et al, 2016;Janšto et al, 2019;MacUra et al, 2019;Siddiqui, 2018).…”
Section: Introductionmentioning
confidence: 99%